The Office of Ra'īs al-ʿUlamā Among the Bosniaks (Bosnian Muslims) - Karčić, Fikret (Intellectual Discourse, 2013)
This paper investigates the origins, the legitimacy and the procedure of the appointment of a Ra’īs al-ʿUlamā’, the religious leader of Bosniaks (Bosnian Muslims). The answers have been sought in the tradition of the Osmanli learned hierarchy, Muslim documents of that period, and the post- Osmanli history of Bosnia. It has been found that the title of Ra'īs al-ʿUlamā’, today only used by Bosniaks to denote their religious leader, has been borrowed from the Osmanli organization of ʿulamā’, that the legality of his office had been provided by referring to Ḥanafī texts on the appointment of governors and judges for Muslims under non-Muslim rule, and that a formal letter of appointment, called manshūr, continues to be issued for newly elected Ra’īs al-ʿUlamā’.